PENGARUH SUHU DAN SALINITAS TERHADAP RESPON FISIOLOGI LARVA TIRAM MUTIARA PINCTADA MAXIMA (JAMESON) - Winanto, Tjahjo; Soedharma, Dedi; Affandi, Ridwan; Sanusi, Harpasis S. (JURNAL BIOLOGI INDONESIA, 2009)
ABSTRACTPENDAHULUANPinctada maxima adalah spesiesakuakultur yang mempunyai nilaiekonomi tinggi (Taylor et al. 1997). Dipasaran internasional, mutiara yangdiproduksi sering kali disebut dengannama ?South Sea Pearl?. Indonesiatermasuk salah satu negara penghasilmutiara (South Sea Pearl) yang cukupdiskenal di pasaran dunia, sebagian besarproduksi South Sea Pearl yang dipasarkanberasal dari hasil budidaya (Anna2006). Produksi mutiara berbasisbudidaya merupakan aktivitas usaha yangmenguntungkan. Perkembangan usahabudidaya mutiara saat ini sudah mengarahpada kegiatan industri yang terintegrasi(Fassler 1995).The Effect of Temperature and Salinity to The Physiological Respons on The Larvae ofPinctada maxima (Jameson). Energy budget is one of the most sensitive tools available forindividual assessing environmental changes like temperature and salinity, and also prerequisitefor individual growth and survival. The aim of this study is to obtained information on energybudget on routine metabolism, in different levels of temperature and salinity, and to know thelevels of optimum temperature and salinity. The research was used randomized block design,with three replications. The result showed that optimal temperature and salinity on P. maximalarvae was 28 oC and 32 ? 34 ? (BE and BF). Energy budget to routine metabolism increasedwas attributed to increased temperature and salinity due to the optimal, than would be decreasedwhen temperature and salinity increased. The highest of energy budged for routine metabolismat treatment BF. Stage I: energy budged between 6.73 ? 7.35 C g wet weight-1 hour-1 (28.18 ?30.74 J g wet weight-1 hour-1); Stages II: 5.85 ? 5.95 C g wet weight-1 hour-1 (24.48 ? 24.90 J g wetweight-1 hour-1); Stages III: 4.73 ? 4.80 C g wet weight-1 hour-1 (15.07? 19.58 J g wet weight-1hour-1). The highest survival rate of larvae was by treatment BF, but has not higher significant(P e? 0.05) with BE, stage I: survival rate between 87.75 ? 87.92 %; Stage II: 81.91 ? 82.39 % andstage III: 76.72 ? 77.26 %. The best of relative growth length of larvae by treatment BF and notsignificant (P e? 0.05) with BE, at stage I: 29.78 x 17.93 ?m ? 30.57 x 18.43 ?m (AP x DV); stageII: 57.62 x 46.73 ?m ? 58.13 x 47.33 ?m and stage III: 80.32 x 69.29 ?m ? 80.88 x 69.62 ?m. Thequickest time of plantigrade stages have found by treatment BF (day 19.50) and hasn?tsignificant (P > 0.05) with BE (day 20.85).Keywords: Pinctada maxima, larvae, response; physiology, metabolism.Kata kunci: Pinctada maxima, larvae, respon, fisiology, metabolisme.